Denpasar Mayor's Instructions on Dengue Fever Mitigation: A Reflection on Sustainable Development - Putu Unilawati; Anom Sapariati; Ida Ayu Putu Sri Widnyani; I Wayan Astawa (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Dengue fever (DHF) is one of the serious infectious diseases in Indonesia, including in the city of Denpasar, which often faces a spike in cases. Dengue fever control requires an integrated and sustainable approach, especially in the context of sustainable development which is the focus of the government. The instructions of the Mayor of Denpasar in this case play an important role in directing local policies to address this problem effectively. This study aims to analyze the instructions of the Mayor of Denpasar in mitigating dengue fever cases and their impact on sustainable development through a normative legal approach. This study uses a procedure that emphasizes the disclosure of truth through the logic of legal science from a normative aspect. Emphasis is placed on the importance of good environmental management, because without it, stopping dengue fever cases will be difficult to achieve. Dengue fever cases require policies that are not only effective in reducing the prevalence of the disease but also contribute to achieving sustainable development goals. Using the normative legal method, this study will examine the regulations and legal instructions issued by the local government and their implementation within the legal framework. This study will also evaluate how these mitigation policies support sustainable development and contribute to the vision of Golden Indonesia 2045. The results of this study are expected to provide insight into the legal strength and effectiveness of policies in addressing health issues while supporting sustainable development.